Flowering ability and expression of the shLFY (shallot-LFY) gene in several Indonesian shallot (Allium cepa, aggregatum group) varieties - JEKKI IRAWAN; DINY DINARTI; SUDARSONO SUDARSONO; AWANG MAHARIJAYA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Irawan J, Dinarti D, Sudarsono, Maharijaya A. 2021. Flowering ability and expression of the shLFY (shallot-LFY) gene in several Indonesian shallot (Allium cepa, aggregatum group) varieties. Biodiversitas 22: 5468-5474. Indonesian shallots (Allium cepa, Aggregatum group) have different flowering abilities. The direction of seed development in the form of true seed shallot (TSS) makes the study of shallot flowering important to support its breeding program. Flowering genes’ presence and their expression demonstrate their significance in inducing flowering. This study aimed to determine the ability of the shLFY gene expression in four shallots varieties (Bima Brebes, Batu Ijo, Biru Lancor, and Sumenep) and the level of expression in each variety during the formation of flower primordia. The research was arranged in a randomized complete block design (RCBD) with varieties as a single factor, for qRT-PCR relative expression data analysis using ??CT comparative method. The results showed that there were differences in flowering ability and the expression value of the shLFY gene between the tested shallot varieties. These differences also were shown within each variety when the umbels of varying ages were tested. There was a positive correlation between the ability to flower and the shLFY gene expression value. The greater shLFY gene expression will be followed by greater flowering ability. Bima Brebes was the variety with the highest flowering ability (91.66%) and highest shLFY gene expression value between other varieties.